Alex Cross, run [compact disc, unabridged] - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2013)
A young woman is found hanging from a sixth-floor window, and Alex is called to the scene. The victim recently gave birth, but the baby is nowhere to be found. Before Alex can begin searching for the missing newborn and killer, he's called to investigate a second crime.